Understanding and using English grammar - Azar, Betty Schrampfer; Hagen, Stacy A. (Hoboken, NJ, USA : Pearson Education, 2009)
A workbook for intermediate to advanced English learners, combining a grammar-based approach with carefully sequenced practice to help the development of all language skills. Self-study exercises, with the answer key included, provide students with the opportunity to explore and practice grammar independently. It is keyed to the explanatory grammar charts in both the Student Book and the Chartbook.
Keywords: English language -- Textbooks for foreign speakers -- Study and teaching; English language -- Problems, exercises, etc. -- Grammar